(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aimed to analyze the role of Climate-Smart Agriculture (CSA) in supporting sustainable agricultural development and enhancing food security in the Arab world under increasing climate change challenges. The study adopted a descriptive-analytical approach through reviewing and analyzing recent scientific literature and international reports related to climate-smart agriculture, modern agricultural technologies, and agricultural artificial intelligence applications. The findings revealed that climate-smart agriculture technologies, including artificial intelligence, precision agriculture, remote sensing, and expert systems, significantly contribute to improving the efficiency of natural resource management, reducing agricultural losses, enhancing crop quality, and strengthening the resilience of agricultural systems against climate change impacts. The study also indicated that successful transformation toward climate-smart agriculture requires the development of digital agricultural infrastructure, support for agricultural scientific research, and the establishment of integrated agricultural and technological policies that support digital transformation in the Arab agricultural sector. The study concluded that climate-smart agriculture represents one of the most important future approaches for achieving sustainable agricultural development and enhancing food security in the Arab world.